An Analysis of Happiness Levels Among Adolescents Experiencing Grief Symptoms - Ardha Dwi Anzeli; Gian Sugiana Sugara; Agung Nugraha (Edupotensia, 2025)
This study aims to describe the level of happiness among adolescents experiencing grief symptoms. The research employed a quantitative approach with a descriptive design. The sample consisted of 125 adolescents, selected using a purposive sampling technique. The instruments used were the Prolonged Grief Disorder – Revised (PG-13-R) to identify grief symptoms and the PERMA Profiler to measure happiness levels. The findings showed that the majority of students were in the normal grief category (77.6%), while 10.4% experienced syndromal level symptomatology and 12% were classified as prolonged grief disorder. Regarding happiness levels, most students were in the moderate category (74.4%), with smaller proportions in the low (12.8%) and high (12.8%) categories. These results indicate that although most adolescents are in the normal grief category and show moderate happiness levels, preventive efforts and counseling interventions are still needed to enhance their happiness.